HAPPi Kneecaps! Protocol for a participant- and assessor-blinded, randomised, parallel group feasibility trial of foot orthoses for adolescents with patellofemoral pain - Isobel C. O’Sullivan; Kay M. Crossley; Steven J. Kamper; Marienke van Middelkoop; Bill Vicenzino; Melinda M. Franettovich Smith; Hylton B. Menz; Anne J. Smith; Kylie Tucker; Karina T. O’Leary; Natalie J. Collins (Journal of Foot and Ankle Research, 2020)
Abstract Background Patellofemoral pain (PFP) is a common cause of knee pain in adolescents, but there are limited evidence-based treatment options for this population. Foot orthoses can improve pain and function in adults with PFP, and may be effective for adolescents. The primary aim of this study is to determine the feasibility of conducting a full-scale randomised controlled trial (RCT) evaluating the effects of contoured foot orthoses on knee pain severity and patient-perceived global change, compared to flat shoe insoles, in adolescents with PFP. The secondary aim is to provide an estimate of treatment effects for foot orthoses, compared to flat insoles, in adolescents with PFP. Methods This randomised, controlled, participant- and assessor-blinded, feasibility trial has two parallel groups. Forty adolescents (aged 12–18 years) with clinical symptoms of PFP will be recruited from Queensland, Australia. Participants will be randomised to receive either prefabricated contoured foot orthoses or flat shoe insoles. Both interventions will be fit by a physiotherapist, and worn for 3 months. Feasibility will be evaluated through assessing willingness of volunteers to enrol, number of eligible participants, recruitment rate, adherence with the study protocol, adverse effects, success of blinding, and drop-out rate. Secondary outcomes will evaluate knee-related pain, symptoms, function, quality of life, global rating of change, patient acceptable symptom state, and use of co-interventions, at 6 weeks and 3 months. Primary outcomes will be reported descriptively, while estimates of standard deviation and between-group differences (with 95% confidence intervals) will be reported for secondary outcomes. Discussion Findings of this study will inform the feasibility of a full-scale RCT investigating the efficacy of contoured foot orthoses in adolescents with PFP. This full-scale study is necessary to improve the evidence base for management of adolescent PFP, and enhance outcomes for this population. Trial registration ACTRN12619000957190 .